MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP MUHAMMADIYAH 29 PADANGSIDIMPUAN - Darliana Sormin (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2017)
This study discusses the principal's management in improving the quality   of   education   in   midle   school   Muhammadiyah   29 Padangsidimpuan.  The  purpose  of  this  study  is  to  find  out  how the   planning   and   implementation   of   school   principals   in improving  the  quality  of  education  in  midle  school Muhammadiyah  29  Padangsidimpuan.  The  type  of  this  research is  qualitative  descriptive  by  using  interview,  observation,  and documentation as data collection. Analyze data by compiling data, managing data, then describing it systematically. The result of the principal's  management  in  improving  the  quality  of  education  at midle   school   Muhammadiyah   29   Padangsidimpuan   is   the principal  conducting  meetings  to  plan  the  annual  program,  then the results of the meeting will be socialized to teachers, students, parents  and  school  committees,  then  in  improving  the  quality  of principals'   Activities   such   as:   pengajian,   muhadarah   by presenting   ustadz,   practice   of   prayer,   then   familiarize   the students to be close to the Qur'an by doing activities one day one verse  of  a  verse  done  in  rotation  and  in  reading  every  morning apple. Then in the process of learning the principal suggests that teachers   use   varied   methods,   discipline   of   the   class   entry schedule,   the   existence   of   job   accountability,   deliberation   in deciding   a   problem,   openness   in   terms   of   costing   fees   and development money